The major breakthrough of the 21st century- HPV Vaccine - Singh, Mita (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–>doi:10.3126/njog.v2i2.1445 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 1 - 2